DIFFERENCES IN HEMOGLOBIN LEVELS AND BODY WEIGHT OF THIRD TRIMESTER PREGNANT WOMEN BASED ON COMPLIANCE WITH IRON TABLETS AT CLINIC DENIAWATI IN 2021 - Setia Sihombing (Institute of Computer Science (IOCS), 2021)
Pregnancy is a special condition for a woman as a prospective mother because there will be physical changes that will affect her life during pregnancy. Diet and lifestyle can help the growth and development of the fetus in the mother's womb. (Irianto, 2015) The results of the 2018 Riskesdas show that the proportion of anemia in pregnant women from 2013 to 2018 has increased by 11.8%; in 2013, the proportion was 37.1%, and in 2018 the proportion was 48.9% (Riskesdas, 2018 ). This study aims to determine differences in hemoglobin levels and body weight of pregnant women in the third trimester based on adherence to iron tablets at the Deniawati Clinic in 2021. This study uses a comparative quantitative approach. This study's sample number was 26 pregnant women in the third trimester. The results showed a 2-way (t-tailed) significance value of 0.000 < 0.05 and 0.003 < 0.005. Conclusion this means that there are significant differences in the hemoglobin levels and body weight of pregnant women between obedient and non-adherent mothers taking iron tablets during pregnancy. This study recommends that further researchers need to conduct further research with different variables that are deeper.